PENGARUH PENGGUNAAN MEDIA KARTU KATA AKSARA LONTARA MAKASSAR TERHADAP KETERAMPILAN MEMBACA SISWA KELAS III SDI LIMBUNG KECAMATAN BAJENG KABUPATEN GOWA - Ainun Fitri Delila; Aco Karumpa; Syekh Adiwijaya Latief (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of Makassar Lontara script word-card learning media on the reading skills of third-grade students at SDI Limbung. The research problem was the low reading ability of students in the local language subject, particularly in reading the Lontara script. This study employed a quantitative approach with an experimental method using a One Group Pretest-Posttest Design. The sample consisted of 22 students. Data were collected through tests and observations. The results showed an improvement in students’ reading skills after the implementation of the word-card media. The average pretest score of 61.14 increased to 88.64 in the posttest, while learning mastery improved from 18.18% to 81.82%. Observation results indicated that both teacher and student activities reached 90%, categorized as very good. Hypothesis testing using the t-test showed a t-value of 12.91 and a critical t-value of 2.080 at a significance level of 0.05. Since the t-value was higher than the critical t-value, H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Makassar Lontara script word-card media had a significant effect on students’ reading skills and supported the preservation of local culture in elementary schools.